2015
DOI: 10.1002/ijop.12139
|View full text |Cite
|
Sign up to set email alerts
|

The effects of brief prayer on the experience of forgiveness: An American and Indian comparison

Abstract: The present study offers a cross-cultural examination of the effect of prayer on forgiveness. American (n = 51) and Indian (n = 100) participants either prayed for their romantic partner (prayer condition) or described their romantic partner's physical attributes (control condition). Prayers were self-guided and lasted 3 minutes. Pre-test and post-test measures of retaliation were completed. Results showed that participants in the prayer group showed statistically significant decreases in retaliation motives f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…While religion (Rye & McCabe, 2014), empathy (Toussaint & Webb, 2005), prayer (Toussaint, Kamble, Marschall, & Duggi, 2016), and preexisting relational quality (McCullough et al, 1998) have been found to predict self- and other-forgiveness, the results of the current study demonstrate that grit also stands to meaningfully contribute to our understanding of this important, inter- and intra-personal experience. With a positive sense of self and meaningful interpersonal relationships being such fundamental psychological needs, and assuming that personal shortcomings and interpersonal conflicts are not likely to disappear, it would seem a worthy endeavor to understand the mechanisms through which authentic self- and other-forgiveness can be supported.…”
Section: Discussionmentioning
confidence: 50%
“…While religion (Rye & McCabe, 2014), empathy (Toussaint & Webb, 2005), prayer (Toussaint, Kamble, Marschall, & Duggi, 2016), and preexisting relational quality (McCullough et al, 1998) have been found to predict self- and other-forgiveness, the results of the current study demonstrate that grit also stands to meaningfully contribute to our understanding of this important, inter- and intra-personal experience. With a positive sense of self and meaningful interpersonal relationships being such fundamental psychological needs, and assuming that personal shortcomings and interpersonal conflicts are not likely to disappear, it would seem a worthy endeavor to understand the mechanisms through which authentic self- and other-forgiveness can be supported.…”
Section: Discussionmentioning
confidence: 50%
“…Vasiliauskas and McMinn (2013) conducted a randomized controlled trial with Christians (two experimental conditions: prayer or religious devotion). Participants who prayed for their offender increased empathy, religious commitment, and forgiveness the most (see also Toussaint et al, 2016). Those in the religious-devotion intervention reported less increased forgiveness than those in the prayer condition but more than those in the control condition.…”
Section: Interventions Aimed At Spiritual Practices Hypothesized To I...mentioning
confidence: 86%
“…Vasiliauskas and McMinn (2013) conducted a randomized controlled trial with Christians (two experimental conditions: prayer or religious devotion). Participants who prayed for their offender increased empathy, religious commitment, and forgiveness the most (see also Toussaint et al, 2016). Those in the religious-devotion intervention reported less increased forgiveness than those in the prayer condition but more than those in the control condition.…”
Section: Interventions Aimed At Spiritual Practices Hypothesized To I...mentioning
confidence: 86%